A Facile Surfactant-assisted Synthesis of Graphene Oxide/Zinc Oxide Catalyst for the Degradation of Methylene Blue Dye - Azmi Mohamed, Suriani Abu Bakar (Tanjung Malim, 2024)
A Facile Surfactant-assisted Synthesis of Graphene Oxide/Zinc Oxide Catalyst for the Degradation of Methylene Blue Dye by Azmi Mohamed, Suriani Abu Bakar